Impact of the COVID-19 pandemic on the formal labor market and the pension system in El Salvador - Nelson Fuentes; Gonzalo Aguilar; Camila Trillos (Inter-American Development Bank (IDB), 2022)
Using an impact evaluation methodology for interrupted time-series and the IDB Pension Projection Model, this study estimates that the COVID-19 pandemic could have notably effects on the private pension system in El Salvador as a consequence of the relaxation of requirements to repay early withdrawals that was established in the context of the pandemic. This fact could negatively affect passive coverage rate, system incomes, short-run system surplus and replacement rates, generating an increase in the fiscal cost. The problems of the Salvadoran pension system are structural, and the COVID-19 pandemic has exacerbated them. Consequently, although it is possible to discuss policies to reduce these effects, it is necessary to frame this discussion in the context of a comprehensive reform of the system.
Keywords: C22; G28; H55; J14; J32; J33; 330; COVID-19; Salvadoran pension system; Early Withdrawals; Impactevaluation; Pension reform